Analysing the Works of a Machine Translation - Setiawan, Dedy (International Journal of Language and Literary Studies, 2020)
Machine translation has been around for years. This application is now used frequently in social media with texts which are usually short and simple and found in daily lives. The machine translation has undergone a great progress from the time it was introduced to public in early 2000’s. However, there has been no research to see the performance of the machine translation work.The present research is intended to analyse the works of machine translation with the objects which are complicated scientific texts as found in journal articles. It is intended to see if the result of machine translation is comprehensible, accurate and reliable in translating documents. The result suggests that the works of machine translation are found to be comprehensible and reliable for obtaining the meaning of the translated texts, but it does not conform to the standards for publishable criteria. Further works are needed if the translated texts are aimed for publication.